Effects of high-fiber food on gut microbiology and energy metabolism in Eothenomys miletus at different altitudes - Zhang, Wei; Jia, Ting; Zhang, Hao; Zhu, Wanlong (Frontiers in Microbiology, 2023)
Intestinal microorganisms assist the host in digesting complex and difficultly decomposed foods; expand the host’s dietary ecological niche. In order to investigate the effect of high-fiber food on intestinal microorganisms of Eothenomys miletus at different altitudes, exploring the regional differences of intestinal microorganisms and their roles in body mass regulation, we collected E. miletus from Dali (DL) and Xianggelila (XGLL), which were divided into control group, high-fiber group fed with high-fiber diet for 7 days, and refeeding group fed with standard diet for 14 days after high-fiber diet. Using 16S rRNA gene sequencing technology combined with physiological methods, we analyzed the gut microbial diversity, abundance, community structure and related physiological indicators of each group, and explored the effects of high-fiber foods and regions on the diversity, structure of gut microorganisms and physiological indicators. The results showed that high-fiber food affected the food intake and metabolic rate of E. miletus, which also showed regional differences. The intestinal microorganisms of E. miletus obtained energy through the enrichment of fiber degrading bacteria under the condition of high-fiber food, while producing short-chain fatty acids, which participated in processes such as energy metabolism or immune regulation. Moreover, it also affected the colonization of intestinal microorganisms. High-fiber food promoted the enrichment of probiotics in the intestinal microbiota of E. miletus, but pathogenic bacteria also appeared. Therefore, the changes in the composition and diversity of gut microbiota in E. miletus provided important guarantees for their adaptation to high fiber food environments in winter.